Analisis Kepuasan Pengguna Pada Website Registrasi Pendakian Taman Nasional Gunung Merbabu dengan Metode Webqual 4.0 - Marcelinus Kartika Aji Utomo; Johan J. C. Tambotoh (JURIKOM (Jurnal Riset Komputer), 2023)
In today's all-digital era, the role of technology, namely the Internet, is very influential because all activities can be carried out through cyberspace. All the desired information will be obtained easily and quickly so as to help the movement of society. This information is then poured in a structured and systematic display which is called a website. One website that is known by various groups is https://booking.tngunungmerbabu.org This website is a web-based online service facility provided by Mount Merbabu National Park for tourists who will book tour tickets before visiting tourist sites or climbing. Tourists can register themselves on the system so they don't have to queue and get a quota. However, there are still some problems such as the need to improve website performance which is felt by users. So this study aims to analyze user satisfaction on the Mount Merbabu National Park website using the Webqual 4.0 method based on the dimensions of usability quality, information quality, service interaction quality, and user satisfaction. The research data used 125 data and were processed with SPSS software through validity, reliability, descriptive analysis and multiple linear regression. The results showed that the independent variable (X) studied, namely usability quality, information quality, service interaction quality, had a 46.4% influence on the dependent variable (Y), namely user satisfaction, while the other 53.6% was influenced by other factors outside the variables studied. In measurement using a Likert scale it can be seen that the variable quality of usability, quality of information, quality of service interaction and user satisfaction results in "Strongly Agree" and the measurement level of the website www.booking.tngunungmerbabu.org is adequate and very good.